A Model of Cross-Cultural Language Politeness for Tourists in The Lake Toba Region of Indonesia - Saragih, Elza Leyli Lisnora; Mulyadi, M; Nasution, Khairina; Pujiono, Mhd (Universitas Muhammadiyah Surakarta, 2023)
This paper discusses the politeness model for tourism actors in the Lake Toba area. Today's globalization allows us to easily travel to various parts of the world. Communication between countries with different cultural backgrounds occurs massively. Cultural differences between communicators can lead to understanding. For this reason, this research is very important to do. This study discusses the model of language politeness between countries with a cross-cultural perspective. The research was conducted on local and foreign tourism actors and tourists in the Lake Toba area. This place is the second largest international tourist destination in Indonesia after the island of Bali. This research is a descriptive qualitative using a sociopragmatic approach with cross-cultural studies. Dialogue between tourism actors and tourists is used as a source of data recorded by researchers. Furthermore, the utterances in the dialogue were analyzed using the equivalent and agih techniques. The results of the study show that there are differences in language politeness model between tourists and foreign tourists and domestic tourists.